The content of the stages of musical-animation activities of primary school children - V. V. Levchenkov (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. In recent years, there has been a growing recognition of the role of music and visual arts in the development of creative and musical abilities of primary school children. Sand animation, which combines the synthesis of various types of art, is primarily a musical-animation activity, which makes it more attractive to elementary school students. Musical-animation activities contribute to the development of children’s cognitive abilities, improve social skills and develop creative abilities. Goal. To consider the stages of musical-animation activities of younger schoolchildren in the process of developing their musical-creative abilities. These stages are of practical importance for the learning outcome.Materials and methods. The work mainly used general scientific research methods. Among them, a special role was played by the analysis of scientific literature, observation, systematization, and generalization.Results and discussion. The results of the study show that the stages of musical-animation activity of younger schoolchildren are creation of sand animation, preparation of a musical (vocal) piece; the final product of musical-animation activity; namely a musical-animation work. The application of the described stages in the development of musical-creative abilities in younger schoolchildren makes it possible to achieve high results.Conclusion. Based on the results of our research, we can conclude that music and art education itself plays an important role in the development of younger schoolchildren, contributing to their creative and emotional development. Musical-animation activities of younger schoolchildren in our study involve the joint use of various musical possibilities (vocal-instrumental and instrumental), as well as sand animation (sandpainting), which, in synthesis with music, may develop musical-creative abilities in younger schoolchildren. The study serves as a practical guide for teachers seeking to implement innovative educational strategies in their teaching activities.